Kinetics of devolatilization of oil palm solid wastes using thermo-gravimetric analysis - Abdul Halim Shamsuddin; Paul T. Williams (1992)
The kinetics of the devolatilization of oil palm fibres and shells have been determined in a Thermo-Gravimetric Analyser (TGA). The TGA data indicate that the devolatilization process begins around 200°C and terminates around 600°C. The Differential Thermal Analysis (DTA) data indicate the existence of two different rates of devolatilization with the turning point at around 350°C. The temperature at which the maximum rate of weight loss occurs are around 315°C and 380°C. The kinetic parameters, namely the activation energy and the ftequency factor, are determined assuming a first order reaction. The data are compared to that of pure cellulose